2004
DOI: 10.1038/sj.bjc.6602178
|View full text |Cite
|
Sign up to set email alerts
|

Phase I and pharmacokinetic study of XR11576, an oral topoisomerase I and II inhibitor, administered on days 1–5 of a 3-weekly cycle in patients with advanced solid tumours

Abstract: XR11576 is an oral topoisomerase I and II inhibitor. The objectives of this phase I study were to assess the dose-limiting toxicities (DLTs), to determine the maximum tolerated dose (MTD) and to describe the pharmacokinetics (PKs) of XR11576 when administered orally on days 1 -5 every 3 weeks to patients with advanced solid tumours. Patients were treated with escalating doses of XR11576 at doses ranging from 30 to 180 mg day À1 . For PK analysis, plasma sampling was performed during the first and second course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The pharmacokinetics (PKs) of (20) has been studied in several animal species. In Phase I studies [73], XR11576 (20) was administered orally at a dose of 120 mg per day every 3 weeks, with dose-limiting toxicity consisting of diarrhoea and fatigue. The availability of an oral formulation of (20) for clinical use proved to be a convenient method for prolonged drug administration.…”
Section: Phenazine Derivatives Xr11576 (20) and Xr5944 (21)mentioning
confidence: 99%
“…The pharmacokinetics (PKs) of (20) has been studied in several animal species. In Phase I studies [73], XR11576 (20) was administered orally at a dose of 120 mg per day every 3 weeks, with dose-limiting toxicity consisting of diarrhoea and fatigue. The availability of an oral formulation of (20) for clinical use proved to be a convenient method for prolonged drug administration.…”
Section: Phenazine Derivatives Xr11576 (20) and Xr5944 (21)mentioning
confidence: 99%
“…1) has entered clinical trials. 10 Finally, similar profile was found for TAS-103 (4, Fig. 1), initially identified as dual inhibitor, 11 although it predominantly acts as a topoIIa inhibitor.…”
Section: Introductionmentioning
confidence: 57%
“…Further investigation on the role of topoisomerase inhibition in the mechanism of action of 33, demonstrated that exposure of 33 results in accumulation of topoisomerase I-and II-DNA complexes after long periods, which coincides with the induction of gamma-H2AX foci as a marker for DNA damage (Jobson et al 2009). Although 33 reached Phase I clinical trial in 2004, (de Jonge et al 2004) it was not further pursued because some dimeric phenazine (as XR5944.14 for example) displayed higher activity and therapeutic ratio as detailed below.…”
Section: Phenazine-1-carboxamide and Analogsmentioning
confidence: 99%